Perlindungan Hukum Terhadap Buruh Yang Tidak Mendapatkan Upah Minimum Provinsi (UMP) Dengan Perjanjian Kerja Waktu Tertentu (PKWT) Pada Masa Pandemi - Jihan Fadzillah; Zaini Munawir; Marsella Marsella (Universitas Medan Area, 2022)
The purpose of this study is to determine the form of legal protection for workers who do not get the Provincial Minimum Wage (UMP) with a Specific Time Work Agreement (PKWT) and the mechanism for handling disputes regarding the Provincial Minimum Wage (UMP) which is not fulfilled in a Specific Time Work Agreement (PKWT). at the Manpower Office of North Sumatra Province. The type of research used in writing this thesis is normative juridical which is descriptive analysis. The data collection technique used is library and field. The form of legal protection for workers who do not get the Provincial Minimum Wage (UMP) is that legal protection efforts for these violations are carried out in a preventive and repressive manner. Preventive efforts are to provide guidance as a preventive effort through the dissemination of labor norms, technical advice and assistance. The repressive effort is to give a warning to companies that are suspected of committing wage violations, then review them every 6 (six) months to 1 (one) year. If after the warning and review efforts there are still companies that violate wages, then judicial non-judicial repressive efforts can be carried out. Disputes regarding the Provincial Minimum Wage (UMP) Mechanisms that are Not Fulfilled in a Specific Time Work Agreement (PKWT) at the Manpower Office of North Sumatra Province, can be carried out through mediation, conciliation, arbitration and industrial relations court institutions. Mediation aims to reach or produce an agreement that is acceptable to the disputing parties to end the dispute. Conciliation is carried out by making a collective agreement signed by the parties. Arbitration is conducted by the arbitrator based on the written agreement of the disputing parties.